Usefulness of deep sedation with intravenous dexmedetomidine and midazolam in cardiac catheterization procedures for pediatric patients - Nakamura, Taichi; Iwasaki, Hidenori; Miyazawa, Hanae; Mizutomi, Shinichiro; Imi, Yoko; Ohta, Kunio; Wada, Taizo (Frontiers in Pediatrics, 2024)
Background: Dexmedetomidine (DEX) is a highly selective alpha 2 receptor agonist that has the advantage of causing less respiratory depression than other sedative agents. We evaluated the add-on effects of DEX on sedation among pediatric patients who received midazolam and pentazocine during cardiac catheterization. Methods: 120 cardiac catheterization procedures in 110 patients under deep sedation at Department of Pediatrics, Kanazawa University Hospital from January 2013 to August 2018: 63 procedures without DEX (i.e., non-DEX group) and 57 procedures with DEX (i.e., DEX group). Intravenous midazolam and pentazocine were used in both groups, and DEX without an initial loading dose (0.6 μg/kg/h) was used in the DEX group. We retrospectively investigated complications during catheterization, doses of sedative agents, and changes in vital signs. Results: Hypoxemia requiring oxygen administration during catheterization tended to be higher in the non-DEX group than in the DEX group (4.8% vs. 0%). Additional dose of midazolam was significantly lower in the DEX group (median [IQR]: 0.05 mg/kg [0–0.11]) than in the non-DEX group (0.09 mg/kg [0–0.23], p = 0.0288). The additional dose of midazolam in the non-DEX group with hypoxemia was significantly higher than the dose used in the non-DEX group without hypoxemia. No case of bradycardia below the criteria for bradycardia occurred and no serious complications occurred in the DEX group. Conclusion: The use of intravenous DEX in combination with midazolam and pentazocine in pediatric cardiac catheterization may reduce the need for an additional dose of midazolam and may contribute to the prevention of airway complications associated with respiratory depression caused by sedative agents.